Geoelectrical characterization for liquefaction at coastal zone in South Aceh - Muhammad Syukri (Syiah Kuala University, 2011)
The paper presents a case study of liquefaction investigation, carried out in an area of the South Aceh coast. The zone lies on low flat plain at Tanjung Harapan Village, west coast of Aceh. The process of site investigation is controlled by: occurrence of groundwater, nature of bedrock, and presence of clays. Prediction of liquefaction zones in high seismicity regions will be a great help to mitigate hazards. Geoelectric resistivity using a combination both vertical electrical sounding and horizontal resistivity images of Wenner-Schlumberger configuration have been carried out and can be of help to delineate the liquefaction zones. With this backdrop, it believe that in conjunction with soil and sediment characteristics indicating high susceptibility to liquefaction, and resistivity anomalies will provide vital information to predict and identify the liquefaction zones. Results of this study revealed the surface layer consists of loose sediments, sandy clay, and silty sandy layer are potentially liquefied during earthquake. The 2-D model sections at 10 m electrode spacing were described, together with subsurface structures can be used to predict the resistivity values at a approximately 48 m depth